Membangun Generasi Peserta Didik Berintegritas melalui Kantin Kejujuran - Rusyaid, Rusyaid; Ampesi, Dwi Vira (INCARE, International Journal of Educational Resources, 2025)
This study discusses the implementation of the Honesty Canteen at SMA Negeri 3 Kota Sorong as a character education strategy to instill values of integrity, honesty, and responsibility among students. The background of the research lies in the low level of honesty in educational environments, which impacts the moral formation of the younger generation. The aim of this research is to describe how the honesty canteen program at the school helps shape students with integrity and to identify the challenges encountered in its implementation. This study uses a qualitative descriptive method with a field research approach, involving in-depth interviews, observations, and documentation, analyzed thematically. The results show that the Honesty Canteen, operated without direct supervision or attendants, serves as an effective medium for training student honesty in daily practical situations. However, challenges such as dishonest behavior and financial losses still frequently occur. The school has undertaken several efforts, including reducing product variety, providing regular counseling, and subsidizing funds to sustain the program. This research provides an important contribution to understanding that fostering honest character requires continuous support from all school elements and family education, and when implemented consistently, it can positively impact the development of students into individuals with strong integrity.